Pengaruh Penggunaan Media Visual dalam Meningkatkan Keterlibatan dan Pemahaman Peserta Rapat di kantor YBM BRILiaN Medan - Rini Rahma Safitri; Dara Avira; M Yasir Ardiansyah; Tengku Darmansah (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study discusses the effect of using visual media in improving the engagement and understanding of meeting participants at the YBM BRILiaN Medan office. With a focus on improving participants' attention and focus, understanding of meeting materials, and participants' engagement and participation, this study reveals the positive impact of using visual media in the context of business meetings. The use of visual media, such as multimedia presentations, graphics, and images, proved to be able to increase participants' attention, clarify complex concepts, and motivate participants' active involvement in discussions. The results show that visual media has great potential to strengthen internal communication in YBM BRILiaN Medan offices, by ensuring meeting participants are actively engaged and understand the information presented. As such, this study highlights the importance of judicious use of visual media in designing effective and meaningful meeting sessions. The findings provide valuable insights for the YBM BRILiaN Medan office in developing more effective communication strategies and improving the overall meeting attendee experience.